2006
DOI: 10.1128/jcm.44.2.406-412.2006
|View full text |Cite
|
Sign up to set email alerts
|

Application of Pulsed-Field Gel Electrophoresis To Identify Potential Outbreaks of Campylobacteriosis in New Zealand

Abstract: Since 2002, New Zealand's incidence of campylobacteriosis has exceeded 300 cases per 100,000 people per annum. To evaluate genetic variation in human isolates, 183 Campylobacter isolates were collected from a single clinical laboratory in Christchurch: 77 during an 8-week period in spring, and the rest 3 months later over a second 8-week period in autumn. Isolates were identified to the species level and subtyped using Penner serotyping (Campylobacter jejuni only) and pulsed-field gel electrophoresis (PFGE) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…No follow-up investigation was undertaken to identify common infection sources for these small clusters of cases. A small 2002 study of human cases in the same catchment area as the current study also observed numerous small clusters of cases with indistinguishable PFGE profiles (20). A larger 2009 to 2010 study in the same geographical location (21), which also observed clustering of cases based on PFGE, demonstrated how, even with typing data from human, environmental, and food-related isolates, source identification can be difficult.…”
Section: Fig 2 Cluster Analysis Of Campylobactersupporting
confidence: 52%
“…No follow-up investigation was undertaken to identify common infection sources for these small clusters of cases. A small 2002 study of human cases in the same catchment area as the current study also observed numerous small clusters of cases with indistinguishable PFGE profiles (20). A larger 2009 to 2010 study in the same geographical location (21), which also observed clustering of cases based on PFGE, demonstrated how, even with typing data from human, environmental, and food-related isolates, source identification can be difficult.…”
Section: Fig 2 Cluster Analysis Of Campylobactersupporting
confidence: 52%
“…In addition, our results indicate the P-BIT approach to be more discriminatory than MLST and SmaI-based PFGE typing, another important feature. We found KpnI-based PFGE typing to be the most discriminatory of the methods used in our study, notwithstanding that not all strains prove typeable with this enzyme (18).…”
Section: Discussionmentioning
confidence: 54%
“…Some C. jejuni strains resist digestion with certain restriction enzymes, making characterization by PFGE typing problematic (13,18), while MLST target genes may not always provide data appropriate for the scheme (40). P-BIT relies on a code derived from positive or negative results of PCR analyses for a wide range of genes widely distributed in C. jejuni genomes and extrachromosomal elements and thus offers complete typeability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper describes the analysis by PFGE of more than one isolate of Campylobacter from each of 49 human cases of campylobacteriosis. Between April 2009 and February 2010, 673 clinical isolates of Campylobacter were obtained from clinical laboratories in Christchurch, New Zealand, as previously described (6). Isolates were identified as Campylobacter jejuni, C. coli, or C. lari using PCR assays (2,16), and PFGE analysis was performed as previously described (6), using the restriction enzymes SmaI and KpnI.…”
mentioning
confidence: 99%